Values in Dongeng Ditioeng Memeh Hoedjan by Prince Aria Soeria Atmadja for Civic Education: Ethno-pedagogical Study - Jakawali, Gifari; Jamal, Mujtaba; Rahman, Rahman; Robandi, Babang (Jurnal Lingua Idea, 2023)
"Ditioeng Memeh Hoedjan" is an ancient literary fable that was created and written by Pangeran Aria Soeria Atmajda, who was also the 20th Regent of Sumedang (1883-1919). This fable contains character values that portray virtuous behaviours that every individual should possess. This study aims to describe and analyze the character values contained in the fable "Ditioeng Memeh Hoedjan" using Sundanese ethno-pedagogical perspectives. The analysis of this fable will be further transformed into a Lesson Plan (RPP) for teaching Civics Education to elementary school students. The research method employed in this study is qualitative descriptive. The data for this research were obtained from the manuscript of the "Ditioeng Memeh Hoedjan" fable, which is housed in the Geusan Ulun Museum in Sumedang. The research findings indicate that out of the ten pages in this fable, ten paragraphs contain character values. Based on the classification, four paragraphs discuss religious values, 1 paragraph discusses integrity values, three paragraphs discuss tolerance values, and two paragraphs discuss creative values. The analysis of these values demonstrates positive behaviours that we can emulate to become knowledgeable individuals, far from being arrogant or conceited. These values can mainly be applied to elementary school students in Civics Education, which upholds the values of Pancasila, such as being obedient to religion, exhibiting friendly behaviour, acquiring knowledge, and avoiding harmful behaviours.